Employee training and development - Noe, Raymond A. (New York, NY : McGrawHill Education, 2023)
"Traditionally, training and development were not viewed as activities that could help companies create "value" and successfully deal with competitive challenges. Today, that view has changed. Companies that use innovative training and development practices are likely to report better financial performance than their competitors that do not. Training and development also help a company develop the human capital needed to meet competitive challenges"--
PART ONE: THE CONTEXT FOR TRAINING AND DEVELOPMENTCHAPTER 1: Introduction to Employee Training and DevelopmentCHAPTER 2: Strategic TrainingPART TWO: DESIGNING TRAININGCHAPTER 3: Needs AssessmentCHAPTER 4: Learning and Transfer of TrainingCHAPTER 5: Program DesignCHPATER 6: Training EvaluationPART THREE: TRAINING AND DEVELOPMENT METHODSCHAPTER 7: Traditional Training MethodsCHAPTER 8: Technology-Based Training MethodsCHAPTER 9: Employee Development and Career ManagementPART FOUR: SOCIAL RESPONSIBILITY AND THE FUTURECHAPTER 10: Social Responsibility: Legal Issues, Managing Diversity, and Career ChallengesCHAPTER 11: The Future of Training and Development
This International Student Edition is for use outside of the US
Includes bibliographical references and index.
CBA
Text in English
Keywords: Employees -- Training of